2001
DOI: 10.1038/sj.neo.7900154
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mutation Scanning of Genes Associated with Familial Cancer Syndromes Using Denaturing High-Performance Liquid Chromatography

Abstract: Germline mutations in tumor suppressor genes, or less frequently oncogenes, have been identified in up to 19 familial cancer syndromes including Li-Fraumeni syndrome, familial paraganglioma, familial adenomatous polyposis coli and breast and ovarian cancers. Multiple genes have been associated with some syndromes as approximately 26 genes have been linked to the development of these familial cancers. With this increased knowledge of the molecular determinants of familial cancer comes an equal expectation for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The previously used mutation screening strategy in our laboratory for MEN1 (Crépin et al 2003) required the combination of the two techniques (MDGA and HMA) to yield 100% sensitivity and was therefore much more time consuming and expensive. Marsh et al (2001) and Roberts et al (2001) showed that DHPLC is well adapted to rapid mutation scanning. Due to frequent polymorphisms, especially in exon 9, DHPLC patterns could hide another mutation in the polymorphic DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The previously used mutation screening strategy in our laboratory for MEN1 (Crépin et al 2003) required the combination of the two techniques (MDGA and HMA) to yield 100% sensitivity and was therefore much more time consuming and expensive. Marsh et al (2001) and Roberts et al (2001) showed that DHPLC is well adapted to rapid mutation scanning. Due to frequent polymorphisms, especially in exon 9, DHPLC patterns could hide another mutation in the polymorphic DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…35 In brief, a 5-l aliquot of heteroduplex enhanced PCR product was injected into the mobile phase in the direction of the flow path of the DNASep cartridge (Transgenomic Inc.). The conditions for each amplicon are listed in Table 3.…”
Section: Dhplcmentioning
confidence: 99%
“…34 Mutation scanning by DHPLC has been successfully applied to a number of tumor suppressor genes including PTEN, VHL, and RET. 35 A limitation of this and other mutation scanning techniques is likely interference from the detection of common polymorphisms. An anticipated problem specific to tumor suppressor genes is the possibility of false negative results attributable to LOH when testing tumor DNA.…”
mentioning
confidence: 99%
“…Many different prescreening methodologies have been applied to breast cancer genes, including denaturing gradient gel electrophoresis (6,7 ), single-strand conformation polymorphism analysis (8,9 ), heteroduplex analysis (10 ), conformation-sensitive gel electrophoresis (11,12 ), denaturing HPLC (13 ), and mismatch-cleavage assays (14 ). The throughput of these techniques is limited, however, and their diagnostic accuracies have generally been poorly reported in the literature (15 ).…”
mentioning
confidence: 99%